2006
DOI: 10.1590/s0100-879x2006000600006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of store-operated Ca2+ entry by cyclic-ADP-ribose

Abstract: Store-operated Ca 2+ entry plays an important role in Ca 2+ homeostasis in cells but the mechanisms of control of these channels are not completely understood. We describe an investigation of the role of the CD38-cyclic-ADP-ribose (cADPR)-ryanodine-channel (RyR) signaling pathway in store-operated Ca 2+ entry in human smooth muscle. We observed that human myometrial cells have a functional storeoperated Ca 2+ entry mechanism. Furthermore, we observed the presence of transient receptor potential 1, 3, 4, 5, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…This interpretation would be consistent with a previous study showing that linalool, the major component of neroli, evoked intracellular Ca 2+ release in human cells [20]. However, since ruthenium red decreases store-operated Ca 2+ entry [21], it is more likely that neroli inhibits a RyR-dependent, storeoperated Ca 2+ entry pathway rather than directly affecting intracellular Ca 2+ release. Neroli essential oil and its main components, commonly used in foods and as a natural complement to standard therapies, are known to exert relaxation effects [16].…”
Section: Discussionsupporting
confidence: 92%
“…This interpretation would be consistent with a previous study showing that linalool, the major component of neroli, evoked intracellular Ca 2+ release in human cells [20]. However, since ruthenium red decreases store-operated Ca 2+ entry [21], it is more likely that neroli inhibits a RyR-dependent, storeoperated Ca 2+ entry pathway rather than directly affecting intracellular Ca 2+ release. Neroli essential oil and its main components, commonly used in foods and as a natural complement to standard therapies, are known to exert relaxation effects [16].…”
Section: Discussionsupporting
confidence: 92%
“…5 -8 This is also consistent with the observations that the endogenous RyR agonist cyclic-ADP-ribose (cADPR) activated Ca 2+ influx in human myometrial cells and in RyR1 and TRPC3 coexpressing HEK293 cells; and the cADPR inhibitor 8-Br-cADPR attenuated Ca 2+ influx induced by endothelin-1 in myometrial cells. 7,15 However, it is in contrast to the early study in canine PASMCs that depletion of both InsP 3 R-and RyR-sensitive Ca 2+ stores are required to elicit SOCE. 30,31 Since vasoactive agonist was not used in our experiments and inhibition of InsP 3 R with xestospongin C did not affect RyRmediated Ca 2+ entry, our results clearly show that stimulation of RyR can independently activate SOCE in rat PASMCs.…”
Section: Discussionmentioning
confidence: 94%
“…These data are consistent with studies in other tissues showing CD38 modulation of influx via different channels, although not necessarily SOCE. Indeed, only one other study in myometrial smooth muscle has demonstrated CD38 modulation of SOCE (54).…”
Section: Discussionmentioning
confidence: 99%